Implementasi Karakter Berdasarkan Buah Roh ke dalam Tema-Tema Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VII SMP - Bhaktiar Sihombing; Mintoni Asmo Tobing; Alon Mandimpu Nainggolan (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2022)
This article proposes several characters based on Galatians 5:22-23 that can be implemented into the themes of Christian Religious Education (PAK) or Budi Pekerti that have been determined by the Ministry of Education and Culture (Kemdikbud) of the Republic of Indonesia at the junior high school (SMP) class VII. The type of research method used by the author is a descriptive method, namely by discussing the developmental psychology of junior high school students, the themes of PAK and Budi Pekerti according to the Ministry of Education and Culture, exploring character values based on the fruit of the Spirit in Galatians 5:22-23. Then, in the end, the author will implement these character values into the PAK and Budi Pekerti curriculum that has been prepared by the Ministry of Education and Culture (Kemdikbud).